Graphene: The Missing Piece for Cancer Diagnosis? - Cruz, Sandra M. A. (2016)
This paper reviews recent advances in graphene-based biosensors development in order to obtain smaller and more portable devices with better performance for earlier cancer detection. In fact, the potential of Graphene for sensitive detection and chemical/biological free-label applications results from its exceptional physicochemical properties such as high electrical and thermal conductivity, aspect-ratio, optical transparency and remarkable mechanical and chemical stability. Herein we start by providing a general overview of the types of graphene and its derivatives, briefly describing the synthesis procedure and main properties. It follows the reference to different routes to engineer the graphene surface for sensing applications with organic biomolecules and nanoparticles for the development of advanced biosensing platforms able to detect/quantify the characteristic cancer biomolecules in biological fluids or overexpressed on cancerous cells surface with elevated sensitivity, selectivity and stability. We then describe the application of graphene in optical imaging methods such as photoluminescence and Raman imaging, electrochemical sensors for enzymatic biosensing, DNA sensing, and immunosensing. The bioquantification of cancer biomarkers and cells is finally discussed, particularly electrochemical methods such as voltammetry and amperometry which are generally adopted transducing techniques for the development of graphene based sensors for biosensing due to their simplicity, high sensitivity and low-cost. To close, we discuss the major challenges that graphene based biosensors must overcome in order to reach the necessary standards for the early detection of cancer biomarkers by providing reliable information about the patient disease stage.